Effect of Hadacidin on Growth and Adenylosuccinate Synthetase Activity of Dictyostelium discoideum - Rossomando, Edward F. (1978)
The growth of the eucaryotic microorganism Dictyostelium discoideum in liquid culture was completely inhibited by the aspartic acid analog hadacidin (N-formylhydroxyamino-acetic acid). Growth arrest occurred both in chemically defined medium and in complex growth medium containing aspartic acid and AMP precursors such as adenine and adenosine. Although these compounds could not overcome the effect of hadacidin, growth was restored if cells were washed and resuspended in fresh growth medium. Additional experiments showed that D. discoideum contains adenylosuccinate synthetase, the enzyme which catalyzes the synthesis of adenylosuccinate from IMP, aspartic acid, and GTP in the de novo biosynthesis of purines. A partially purified preparation of this enzyme was obtained, and the effect of hadacidin on its activity was studied. We found that maximum inhibition of the D. discoideum activity occurs at a ratio of aspartic acid to hadacidin of 5:1, suggesting that the affinity of the drug for this enzyme is less than for the enzyme from rabbit muscle and plants but greater than for that from Escherichia coli. The effect of the drug can be overcome by a 10-fold excess of aspartic acid, suggesting that the drug acts as a competitive inhibitor. A comparison of the adenylosuccinate synthetase activity levels at various stages of growth showed that its specific activity decreases about 60% as cells enter the stationary growth phase, and decreases about 75% after starvation for 2 h. Further studies showed that in cells treated with hadacidin the rate of uptake of exogenous nutrients is reduced about 75% and that these cells are more resistant to rupture by osmotic shock. While the results of this study are consistent with the proposal that growth arrest is contingent upon inhibition of adenylosuccinate synthetase activity, they also suggest that, as a consequence of this inhibition, some physiological properties of the cell have been altered.